A Systematic Survey of Carbonic Anhydrase mRNA Expression During Mammalian Inner Ear Development. Issue 3 (28th January 2013) - Wu, Ling; Sagong, Borum; Choi, Jae Young; Kim, Un‐Kyung; Bok, Jinwoong
<x xml:space="preserve">Abstract</x> Background: Carbonic anhydrases (CAs), which catalyze CO2 hydration to bicarbonate and protons, have been suggested to regulate potassium homeostasis and endocochlear potential in the mammalian cochlea. Sixteen mammalian CA isozymes are currently known. To understand the specific roles of CA isozymes in the inner ear, a systematic survey was conducted to reveal temporal and spatial expression patterns of all 16 CA isozymes during inner ear development. Results: Our quantitative reverse transcriptase‐polymerase chain reaction results showed that different tissues express unique combinations of CA isozymes. During inner ear development, transcripts of four cytosolic isozymes (Car1, Car2, Car3, and Car13), two membrane‐bound isozymes (Car12 and Car14), and two CA‐related proteins (Car8 and Car11) were expressed at higher levels than other isozymes. Spatial expression patterns of these isozymes within developing inner ears were determined by in situ hybridization. Each isozyme showed a unique expression pattern during development. For example, Car12 and Car13 expression closely overlapped with Pendrin, an anion exchanger, while Car2 overlapped with Na‐K‐ATPase in type II and IV otic fibrocytes, suggesting functional relationships in the inner ear. Conclusions: The temporal and spatial expression patterns of each CA isozyme suggest unique and differential roles in inner ear development and function. Developmental Dynamics 242:269–280, 2013. © 2012 Wiley Periodicals, Inc.